Equality and non-discrimination of women in the ecuadorian workplace - Muño Subía, Katerine (2021)
The field of labour law in Ecuador has faced the difficulty of guaranteeing the legitimacy of compliance with affirmative ac-tion measures in order to corroborate equal opportunities. The objective of this research is to determine the positivisation of human rights under the Ecuadorian legal system, in relation to equality and non-discrimination of women in the labour sphere. The methodology used was a mixed approach, under the analytical-critical method, as allowed the evaluation about the labour situation of Ecuadorian women, within THE “historical-social” context, the type of legal research responds to the legal-propositional type. In this context, this investigation examined the protection of women’s labour rights from a legal point of view, by analizing the legal framework on equality and non-discrimination. As a result, it was verified that distributive justice has to be applied in the recognition of women’s labour rights in order to achieve equality. In conclusion, labour discrimination is a matter of distributive justice and human dignity and its eradication will allow that women can enjoy the human right to work in order to achieve personal fulfilment